Stable Chiral Complexes of Ionic Liquids with Aluminium and Biaryl Ligands as Efficient Catalysts for the Synthesis of Chiral Lactones - Drożdż, Agnieszka; Foreiter, Magdalena B.; Chrobok, Anna (Synlett, 2014)
A new catalytic system for the asymmetric Baeyer–Villiger oxidation of monosubstituted prochiral cyclobutanones to γ-butyrolactones with high yields (40–99%) and enantioselectivities (45–87%) is described. Aluminium complexes with biaryl ligands and ionic liquids are presented. The incorporation of an ionic liquid in the complex structure was confirmed by the observed four-coordinate nature of the aluminium.
Keywords: ionic liquids; lactones; biaryl ligands; aluminium complexes; asymmetric catalysis